Profiles of executive functions in middle childhood and prediction of later self-regulation - Brandt, Ariadne; Bondü, Rebecca; Elsner, Birgit (Frontiers in Psychology, 2024)
Most research on the development of executive functions (EF) has applied variable-oriented approaches, neglecting the potential inter- and intraindividual interplay of these capacities. In a person-oriented approach, the present study identified varying profiles of performance for three cool EF facets: inhibition, working-memory updating, and cognitive flexibility, as well as two hot EF facets: affective decision-making and delay of gratification, in a community sample of 1,657 children (T1; age: 6-11 years, M=8.36 years, 52.1% female) via latent profile analysis. The best-fitting model allowed for partial dependence across the three cool EF and included four profiles: all-average (69.4% of the children), low-delay (19.0%), regulated-decision-making (7.0%), and low-inhibition (4.6%). Age, binary sex, socio-economic status, multilingualism, and processing speed were identified as significant characteristics of EF profile membership. Longitudinally, a higher probability of belonging to the low-inhibition profile predicted lower rates of the self-regulatory outcome of inhibitory control one year later, while belonging to the regulated-decision-making profile predicted lower rates of the ability to plan and organize three years later. These results not only demonstrate the existence of subgroups with different concurrent within-person expressions of EF performance, but also identify related characteristics and longitudinal outcomes of subgroup membership. In turn, these conclusions stress the importance of person-oriented research to inform on differing weaknesses or strengths in EF performance for varying individuals, thereby providing valuable insight for educational and clinical research into the design of effective personalized support or interventions during middle childhood.